The revivals of the eighteenth century : particularly at Cambuslang. With three sermons / by the Rev. George Whitefield, taken in short hand. Compiled from original manuscripts and contemporary publications. Issued by the Committee of the General assembly of the Free Church of Scotland, for the publication of the works of Scottish reformers and divines. - Macfarlan, D. (Duncan), 1771-1857. (Tufts University. Tisch Library., 2016)
1 online resource (263, 49 pages) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.